War consequences and prospects for post-war reconstruction (case of Ukrainian urban agglomerations) - Kravchenko, Kateryna; Niemets, Liudmyla; Sehida, Kateryna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
During the years of russia’s lasted war against Ukraine, cities and suburbs have become the main centers of military aggression. The restoration and revitalization of territories – particularly cities and urban agglomerations – is a pressing issue, as they serve as concentrators and catalysts for development. Many countries of the world have experience of recovery after large-scale hostilities. Their successful recovery practices should be studied and can be implemented for effective recovery and post-war development of cities and urban agglomerations of Ukraine. The purpose of this study is to identify the key characteristics of the war’s consequences, as well as the challenges and prospects for post-war recovery in Ukraine’s urban agglomerations, incorporating successful global practices and aligning with the goals of sustainable development. This analysis incorporates successful global practices and aligns with the goals of sustainable development. The research aims to develop a flexible recovery model that integrates economic, social, and environmental aspects, adapted to the contemporary challenges facing Ukraine. Results. The study highlights the multidimensional impact of the war on Ukrainian cities, including the physical destruction of infrastructure, socio-economic disintegration, and environmental challenges. Drawing on international experiences of post-war reconstruction in countries such as Germany, Japan, and South Korea, the research identifies effective strategies, including infrastructure modernization, industrial recovery, social integration of internally displaced persons, and land restoration. The article examines urban agglomerations around the world that have experienced significant destruction, including Warsaw, Berlin and Tokyo, and identifies key features of their reconstruction processes. The study emphasizes the importance of rebuilding Ukraine in alignment with the principles and goals of the Concept of Sustainable Development, adhering to the "build back better" strategy. This includes the reuse of "post-war brownfields," the integration of innovative technologies, and the active involvement of local communities in the recovery process. The article outlines the potential for restoring Ukraine’s urban agglomerations and presents a comprehensive set of measures and practical recommendations for the recovery of cities, urban areas, and affected regions. These recommendations are rooted in the framework of the 17 Sustainable Development Goals.